Is God anti-gay? : and other questions about homosexuality, the Bible and same-sex attraction - Allberry, Sam. ([Purcellville, Virginia] : The Good Book Company, 2013)
This book provides a practical and sensitive exploration of the Bible's teaching on homosexuality. It's the hot topic of the moment. Christians, the church and the Bible seem to be out of step with modern attitudes towards homosexuality. And there is growing hostility towards those who hold a different view. So is God homophobic? And what do we say, and how do we relate to to both Christians and non Christians who experience same-sex attraction? In this short, simple book, Sam Allberry wants to help confused Christians understand what God has said about these questions in the scriptures, and offers a positive and liberating way forward through the debate. - Publisher.
Introduction -- Getting started : the Bible, marriage and sex -- The Bible and homosexuality : surely a same-sex partnership is OK if it's commited and faithful? -- But Jesus never mentions homosexuality, so how can it be wrong? -- Homosexuality and the Christian : aren't we just picking and choosing which Old Testament laws apply? -- Homosexuality and the church : can't Christians just agree to differ on this? -- Homosexuality and the world -- Conclusion : what should I do if a Christian comes out to me?
Keywords: Homosexuality -- Biblical teaching; Homosexuality -- Religious aspects -- Christianity